Coffee and Tea Consumption in Relation to Risk of Rheumatoid Arthritis in the Women's Health Initiative Observational Cohort. Issue 3 (April 2019) - Lamichhane, Diman; Collins, Christopher; Constantinescu, Florina; Walitt, Brian; Pettinger, Mary; Parks, Christine; Howard, Barbara V.
Abstract : Objective: The aim of this study was to evaluate whether tea or coffee consumption is associated with an increased risk of older-onset rheumatoid arthritis (RA) using the Women's Health Initiative Observational Study. Methods: The Women's Health Initiative Observational Study is a longitudinal prospective cohort study conducted from 1993 to 1998. There were 76, 853 women who completed a self-administered questionnaire about their daily consumption of tea and coffee. One hundred eighty-five women self-reported and validated incident cases of RA were observed after 3 years of observation. Multivariable Cox proportional hazards models were performed to assess the relationship between consumption habits and disease incidence. Trend tests were calculated using categorical variables modeled as a continuous variable without collapsing. Results: There was no increase in the hazard ratio for incident RA in those participants who drank coffee compared with those who did not. The amount of coffee consumed and the method of preparation (caffeinated/decaffeinated; filtered/unfiltered) also did not alter the risk of incident RA. There was a positive association of incident RA and caffeinated tea consumption in the trend test ( p = 0.03). When assessing any caffeinated tea consumption versus no tea consumption, the hazard ratio for incident RA was 1.40 (confidence interval, 1.01–1.93; p = 0.04). Conclusions: In a large prospective cohort of older women, there was no association between coffee consumption and incident RA. A small association between daily caffeinated, nonherbal tea consumption and incident RA was found.